2014
DOI: 10.1007/s12975-014-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant T Cell Receptor Ligand Treatment Improves Neurological Outcome in the Presence of Tissue Plasminogen Activator in Experimental Ischemic Stroke

Abstract: RTL1000 is a partial human MHC molecule coupled to a human myelin peptide. We previously demonstrated that RTL1000 was protective against experimental ischemic stroke in HLA-DR2 transgenic (DR2-Tg) mice. Since thrombolysis with recombinant tissue plasminogen activator (t-PA) is a standard therapy for stroke, we determined if RTL1000 efficacy is altered when combined with t-PA in experimental stroke. Male DR2-Tg mice underwent 60 min of intraluminal middle cerebral artery occlusion (MCAO). t-PA or vehicle was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…A similar effect has also been demonstrated in young female DR2-Tg mice (Pan et al, 2014). We also confirmed that combining RTL1000 with t-PA does not alter its ability to reduce infarct in experimental ischemic stroke (Zhu et al, 2014B). …”
Section: Introductonsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar effect has also been demonstrated in young female DR2-Tg mice (Pan et al, 2014). We also confirmed that combining RTL1000 with t-PA does not alter its ability to reduce infarct in experimental ischemic stroke (Zhu et al, 2014B). …”
Section: Introductonsupporting
confidence: 75%
“…The dose and injection protocol of RTL1000 was established in our previous studies (Subramanian et al, 2009; Zhu et al, 2014A; Zhu et al, 2014B). …”
Section: Methodsmentioning
confidence: 99%
“…Male HLA-DRB1*1502 transgenic mice (DR2-Tg, 10–14 weeks of age and weighing 23–28 g) were produced at the Portland VA Medical Center using foundation breeders provided by Dr. Chella David [22]. The mice were housed in temperature-controlled rooms on a 12 hour light and 12-hour dark cycle with water and food ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…LDP was measured before CCA ligation (baseline), and measurements continued throughout procedure and 5 min after release of CCA ligature. Animals were excluded if LDP did not drop below 30% of baseline after all thrombin was infused [22]. …”
Section: Methodsmentioning
confidence: 99%
“…First, employment of translatable model systems is essential, e.g. , use of an embolic stroke model that encompasses tPA-induced reperfusion [34, 35]. Future studies are warranted to determine whether early BBB impairment might predict the risk of hemorrhagic transformation upon tPA recanalization and influence stroke prognosis.…”
mentioning
confidence: 99%